2012
DOI: 10.1063/1.3680591
|View full text |Cite
|
Sign up to set email alerts
|

Giant, voltage-actuated deformation of a dielectric elastomer under dead load

Abstract: Far greater voltage-actuated deformation is achievable for a dielectric elastomer under equal-biaxial dead load than under rigid constraint usually employed. Areal strains of 488% are demonstrated. The dead load suppresses electric breakdown, enabling the elastomer to survive the snap-through electromechanical instability. The breakdown voltage is found to increase with the voltage ramp rate. A nonlinear model for viscoelastic dielectric elastomers is developed and shown to be consistent with the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
117
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(120 citation statements)
references
References 20 publications
2
117
1
Order By: Relevance
“…When a voltage is applied to the electrodes, the membrane is squeezed in thickness and expands in plane due to the electrostatic pressure. Giant voltagetriggered deformations up to 360% linear strain with clamped elastomer, 5 488% area strain with membrane under dead loads, 6 and 1692% area strain on membranes mounted on an air chamber 7 have been reported using polyacrylate VHB films from 3 M. However, to achieve reproducible and fast actuation and to prevent creep phenomenon, one must switch from VHB to materials with negligible viscoelastic behavior such as some classes of polydimethylsiloxanes (PDMS) or polyurethanes. Pelrine et al have reported, in 2000, a 117% uniaxial linear strain with an actuator patterned as a long strip on a uniaxially prestretch silicone elastomer.…”
Section: Improved Electromechanical Behavior In Castable Dielectric Ementioning
confidence: 99%
“…When a voltage is applied to the electrodes, the membrane is squeezed in thickness and expands in plane due to the electrostatic pressure. Giant voltagetriggered deformations up to 360% linear strain with clamped elastomer, 5 488% area strain with membrane under dead loads, 6 and 1692% area strain on membranes mounted on an air chamber 7 have been reported using polyacrylate VHB films from 3 M. However, to achieve reproducible and fast actuation and to prevent creep phenomenon, one must switch from VHB to materials with negligible viscoelastic behavior such as some classes of polydimethylsiloxanes (PDMS) or polyurethanes. Pelrine et al have reported, in 2000, a 117% uniaxial linear strain with an actuator patterned as a long strip on a uniaxially prestretch silicone elastomer.…”
Section: Improved Electromechanical Behavior In Castable Dielectric Ementioning
confidence: 99%
“…The mechanical loading configuration was modified from that in our previous work on actuators [11] . Equi-biaxial loading was accomplished by applying radial forces to the circumference of the DE sheet through an assembly of clips, wires (0.23 mm, 1080 carbon steel) and pulleys, all loaded by the motion of a linear servo-motor (Model SLP35, Nippon Pulse America Inc.), which is schematically shown in Figure 1a Figure 1c and 1d, respectively.…”
Section: Mechanical Loading Configurationmentioning
confidence: 99%
“…While large voltage-induced deformation has been demonstrated for an elastomer sheet under equal-biaxial forces, [24][25][26] only small voltage-induced deformation has been observed for an elastomer sheet under a uniaxial force. 27 Many applications, however, require muscle-like actuators in which a voltage induces large and unidirectional displacement.…”
mentioning
confidence: 99%